Magnitude of Financial Distress in Micro, Small and Medium Enterprises (MSMES) in Bihar, India: A Test of Altman Z’ Score - PRAKASH, Bishwajeet; VERMA, Jainendra Kumar (Journal of Advanced Research in Law and Economics; Vol 10 No 4 (2019): JARLE Vol X Issue 4(42) Summer 2019, 2019)
Micro, Small and Medium Enterprises (MSMEs) play a crucial role in equitable upliftment and development of economy. Although these sectors are contributing to economy through generation of employment, supply products, services through indigenous and modern technology, promote social entrepreneurship, reduce regional disparities, and promote equitable income opportunities as well strengthen the balance of trade of the economy. MSMEs are facing actuate deficiency of management which leads to organization in to financial deficiency. Financial Distress in the MSMEs is common for all economy of the world, which has been major concern for the academicians, experts, professional, society, creditors and government. This study identifies the prediction of sickness in MSMEs in Bihar with the help of Altman Z’ Score. The study employs the statistical and financial methods to analyze the data collected in the study. The study identifies financial distress in small and medium enterprises through their balance sheet and profit and loss account. The study came out with proper strategy and policy related to revival of the enterprise from the financial sickness and preventing them from industrial sickness.